2016
DOI: 10.1177/0269216316635387
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for end-of-life care: An updated systematic review

Abstract: Background: Music therapy during palliative and end-of-life care is well established

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 14 publications
(32 reference statements)
1
42
0
2
Order By: Relevance
“…Music/art therapy: However, there was moderatequality evidence from three reviews 51,69,94 demonstrating the positive impact of music/art therapy on a The GRADE category is based on identified systematic reviews published between 2013 and February 2018. We used the following reasons for downgrading confidence in the evidence (downgraded by 1 or 2): Study limitation (observational studies start with a low GRADE value), Inconsistency (individual studies do not come to the same conclusions or there is only one study so inconsistency cannot be evaluated), Imprecision (there is no effect estimate, there is no measure of dispersion, or the CI is very broad); we used the systematic review authors' evaluation for other GRADE criteria if there was a formal quality of evidence assessment (see text).…”
Section: (S)mentioning
confidence: 99%
See 3 more Smart Citations
“…Music/art therapy: However, there was moderatequality evidence from three reviews 51,69,94 demonstrating the positive impact of music/art therapy on a The GRADE category is based on identified systematic reviews published between 2013 and February 2018. We used the following reasons for downgrading confidence in the evidence (downgraded by 1 or 2): Study limitation (observational studies start with a low GRADE value), Inconsistency (individual studies do not come to the same conclusions or there is only one study so inconsistency cannot be evaluated), Imprecision (there is no effect estimate, there is no measure of dispersion, or the CI is very broad); we used the systematic review authors' evaluation for other GRADE criteria if there was a formal quality of evidence assessment (see text).…”
Section: (S)mentioning
confidence: 99%
“…94 Another review found that music therapy was associated with a significant reduction in pain (SMD À0.42; CI À0.68, À0.17; three non-RCT studies). 69 Comprehensive palliative care: There was also moderate-quality evidence for the impact of a comprehensive palliative care team for adults on symptom burden. One review found that comprehensive palliative care was associated with a statistically and clinically significant reduction in symptom burden in adults with advanced illness at 1-to 3-month follow-up (SMD À0.66; CI À1.25, À0.07; 10 RCTs) and at 4-to 6-month follow-up (SMD À0.31; CI À0.05, À0.07; six RCTs.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while music therapy is widely applied for a variety of populations with terminal diseases including paediatrics (e.g. Archie, Bruera, & Cohen, 2013;Bradt & Dileo, 2010;Hilliard, 2005;McConnell, Scott, & Porter, 2016), no publications were found that specifically address music therapy during end-of-life care in the NICU. This suggests that it may not yet be a fully integrated aspect of clinical practice or a currently active field of research.…”
Section: Intr Introduction Oductionmentioning
confidence: 99%